Архітектура розподіленої операційної системи Е1 - Ryzhyk, L. B.; Burtsev, A. Y. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
This paper presents the distributed operating system architecture based on the concept of replication of distributed objects. A complete or partial copy of distributed object’s state is placed in each node where the object is used. Copy coherence is ensured by replication algorithms. For each object the most efficient access algorithm, taking its semantics into account, can be applied. All E1 subsystems are designed to support replication, which makes E1 a convenient platform for developing reliable distributed applications.